2009
DOI: 10.4137/gei.s2918
|View full text |Cite
|
Sign up to set email alerts
|

Low serum Alpha-1 Antitrypsin Associated with Anti-PR-3 AncA in Autistic Children with GI Disease

Abstract: Aim:To assess the possible relationship between serum alpha-1 antitrypsin (AAT) levels and anti-neutrophil cytoplasmic antibodies (ANCA) in autistic children with severe GI disease and to test the hypothesis that there is an association between low serum AAT levels, the presence of ANCA and inflammatory GI disease seen in some autistic children. Subjects and Methods:Serum from 40 autistic children with chronic digestive disease (many with ileo-colonic lymphoid nodular hyperplasia (LNH) and inflammation of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
7

Relationship

5
2

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 32 publications
0
12
1
Order By: Relevance
“…Thus, the complement system in the periphery of subjects with ASD may be activated . Low levels of SERPINA1 have been observed in some children with autism, which is inconsistent with our finding and need further confirmation. Activation of complement pathway can ultimately lead to the release of inflammatory mediators.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…Thus, the complement system in the periphery of subjects with ASD may be activated . Low levels of SERPINA1 have been observed in some children with autism, which is inconsistent with our finding and need further confirmation. Activation of complement pathway can ultimately lead to the release of inflammatory mediators.…”
Section: Discussioncontrasting
confidence: 95%
“…Two proteins, that is, C5 and FERMT3 are being reported for the first time to be associated with autism. Likewise, we performed the FDR (false discovery rate) correction for [20,21] Alpha-1-antitrypsin (+) c) P01009 SERPINA1 37 50 2.07 2.94 4.27 [42,43] Alpha-actinin-1 (−) P12814 ACTN1 28 31 −3.91 −4.89 −4.21 [56,57] Alpha-enolase (−) P06733 ENO1 6 19 −1.02 −1.87 −2.34 [58] Angiotensinogen (+) c) P01019 AGT 21 31 3.31 5.71 4.77 [59] Apolipoprotein E (+) c) P02649 APOE 136 68 1.99 1.42 3.61 [47] Beta [25,61,62] Fibulin-1 (+) P23142 FBLN1 20 15 1.18 1.40 2.41 [31] Insulin-like growth factor -binding protein complex acid labile subunit (+) P35858 IGFALS 9 17 0.82 3.32 1.97 [57] Integrin alpha-IIb (−) P08514 ITGA2B 6 5.6 −2.03 −2.34 −3.23 [26] Kallistatin (+) c) P29622 SERPINA4 7 19 1.67 2.72 1.00 [59] Microtubule-associated protein RP/EB family member 2 (−) [27] a) (+), protein increased in abundant; (−), protein decreased in abundant. b) Fold change (log 2 ratio), p < 0.05 versus the control.…”
Section: Itraq Comparative Proteomics Resultsmentioning
confidence: 99%
“…Evidence suggests that increased oxidative stress is associated with autism, with likely contributions from environmental, 46,47 genetic 4851 and immunological 5258 factors. This may be due to (a) increased production of endogenous pro-oxidants (such as NO, xanthine oxidase, homocysteine) 5964 or environmental pro-oxidants, 65,66 or deficiencies of antioxidants (ceruloplasmin, transferrin, superoxide dismutase, glutathione peroxidase, catalase, reduced glutathione), or both.…”
Section: Discussionmentioning
confidence: 99%
“…30 We have also reported that a significant number of autistic children with chronic digestive disease have anti-PR3 ANCA, low serum AAT, and high serum PR3, which correlate with high severity of GI disease, suggesting that high PR3 levels may be causing ANCA in autistic children with severe GI problems. 31 Because of this, we hypothesized that the autoimmune response in this sub group of autistic children might be general, so we tested the same population for ASCA.…”
Section: Introductionmentioning
confidence: 99%